mTORC2 Deficiency Alters the Metabolic Profile of Conventional Dendritic Cells - Watson, Alicia R.; Dai, Helong; Zheng, Yawen; Nakano, Ryosuke; Giannou, Anastasios D.; Menk, Ashley V.; Stolz, Donna B.; Delgoffe, Greg M.; Thomson, Angus W. (Frontiers in Immunology, 2019)
In myeloid dendritic cells (DC), deletion of the mechanistic target of rapamycin complex 2 (TORC2) results in an augmented pro-inflammatory phenotype and T cell stimulatory activity; however, the underlying mechanism has not been resolved. Here, we demonstrate that mouse bone marrow-derived TORC2-deficient myeloid DC (TORC2-/- DC) utilize an altered metabolic program, characterized by enhanced baseline glycolytic function compared to wild-type WT control (Ctrl) DC, increased dependence on glycolytic ATP production, elevated lipid content and higher viability following stimulation with LPS. In addition, TORC2-/- DC display an increased spare respiratory capacity (SRC) compared to WT Ctrl DC; this metabolic phenotype corresponds with increased mitochondrial mass and mean mitochondrial DNA copy number, and failure of TORC2-/- DC mitochondria to depolarize following LPS stimulation. Our data suggest that the enhanced metabolic activity of TORC2-/- DC may be due to compensatory TORC1 pathway activity, namely increased expression of multiple genes upstream of Akt/TORC1 activity, including the integrin alpha IIb, protein tyrosine kinase 2/focal adhesion kinase, IL-7R and Janus kinase 1(JAK1), and the activation of downstream targets of TORC1, including p70S6K, eukaryotic translation initiation factor 4E binding protein 1 (4EBP1) and CD36 (fatty acid translocase). These enhanced TORC1 pathway activities may culminate in increased expression of the nuclear receptor peroxisome proliferator-activated receptor γ (Pparγ) that regulates fatty acid storage, and the transcription factor sterol regulatory element-binding transcription factor 1 (Srebf1). Taken together, our data suggest that TORC2 may function to restrain TORC1-driven metabolic activity and mitochondrial regulation in myeloid DC.